2020
DOI: 10.1177/2055102920914076
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with antenatal depression among pregnant women in Vietnam: A multisite cross-sectional survey

Abstract: This study aimed to describe the status of antenatal depression and its associated factors among pregnant women in Vietnam. A cross-sectional study was conducted in four obstetric hospitals in Vietnam from January to September 2019. A total of 1260 pregnant women were interviewed using a structured questionnaire. A Tobit regression model was used to determine factors associated with antenatal depression. Results showed that pregnant women were at high risk of antenatal depression (24.5%). Women with fetus abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 27 publications
0
20
1
4
Order By: Relevance
“…14 Futhermore, prolonged depression during pregnancy may elevate the risks of adverse birth outcomes, including premature birth, low birth weight, and delayed development. 3 These adverse outcomes indicate that a comprehensive assessment of mental health is of great signi cance to identify pregnant women who have anxiety or depression during the epidemic.…”
Section: 2cognitive and Behavioral Responses Of Pregnant Women Durmentioning
confidence: 99%
“…14 Futhermore, prolonged depression during pregnancy may elevate the risks of adverse birth outcomes, including premature birth, low birth weight, and delayed development. 3 These adverse outcomes indicate that a comprehensive assessment of mental health is of great signi cance to identify pregnant women who have anxiety or depression during the epidemic.…”
Section: 2cognitive and Behavioral Responses Of Pregnant Women Durmentioning
confidence: 99%
“…14 Futhermore, prolonged depression during pregnancy may elevate the risks of adverse birth outcomes, including premature birth, low birth weight, and delayed development. 3 These adverse outcomes indicated that a comprehensive assessment of mental health was of great importance to identify pregnant women who had anxiety or depression early during the epidemic.…”
Section: 2cognitive and Behavioral Responses Of Pregnant Women Durmentioning
confidence: 99%
“…It was globally estimated that 10% of women have experienced prenatal depression, and the proportion was as high as 15.6% in developing countries. 3 Furthermore, a number of studies demonstrated that nearly 80% of depressive symptoms (with an Edinburgh Postnatal Depression Scale (EPDS) score of 14 or higher) occurred during pregnancy, rather than postpartum. 4 To our knowledge, pregnant women are susceptible to respiratory pathogens and develop severe pneumonia, which may make them more susceptible to COVID-19 infection than general people.…”
Section: Introductionmentioning
confidence: 99%
“…10 Futhermore, prolonged depression during pregnancy may elevate the risks of adverse birth outcomes, including premature birth, low birth weight, and delayed development. 3 These adverse outcomes indicate that a comprehensive assessment of mental health is of great signi cance to identify pregnant women who have anxiety or depression during the epidemic.…”
Section: In Uences Of Covid-19 Outbreak On Pregnant Womenmentioning
confidence: 99%
“…It is globally estimated that 10% of women have experienced prenatal depression, and the proportion is as high as 15.6% in developing countries. 3 Furthermore, a number of studies demonstrated that nearly 80% of depressive symptoms (with an Edinburgh Postnatal Depression Scale (EPDS) score of 14 or higher) occur during pregnancy, rather than postpartum. 4 To our knowledge, pregnant women are susceptible to respiratory pathogens and develop severe pneumonia, which may make them more susceptible to COVID-19 infection than general people.…”
Section: Introductionmentioning
confidence: 99%